2003
DOI: 10.1111/j.1574-6941.2003.tb01066.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of grassland management regime on the community structure of selected bacterial groups in soils

Abstract: The impact of long-term grassland management regimes on microbial community structure in soils was assessed using multivariate analysis of polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) banding patterns of selected bacterial groups and PLFA (phospholipid fatty acid) profiling. The management regimes assessed were inorganic nitrogen (N) fertiliser application and soil drainage. PCR-DGGE profiles of the eubacteria, actinomycetes, ammonia oxidisers and pseudomonads were assessed by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(62 citation statements)
references
References 41 publications
3
56
1
2
Order By: Relevance
“…The lack of explanation by soil variables in the sunny situation is probably due to the high homogeneity of soil conditions. Similarly, Clegg et al (2003) showed no significant relationship between PLFA and soil variables such as organic matter, pH, total C and total N in grasslands. In our study, only pH explained part of the variation in the shady situation where soil conditions were slightly less homogeneous than in the sunny situation ( Figure 2 and Table 2).…”
Section: Potential Metabolic Reactivity At Community Level After Distmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of explanation by soil variables in the sunny situation is probably due to the high homogeneity of soil conditions. Similarly, Clegg et al (2003) showed no significant relationship between PLFA and soil variables such as organic matter, pH, total C and total N in grasslands. In our study, only pH explained part of the variation in the shady situation where soil conditions were slightly less homogeneous than in the sunny situation ( Figure 2 and Table 2).…”
Section: Potential Metabolic Reactivity At Community Level After Distmentioning
confidence: 99%
“…Much research effort has been directed at understanding how agriculture and land use practice influence the structure and diversity of animal and microbial below-ground communities (Chabrerie et al, 2003;Clegg et al, 2003;Grayston et al, 2004;Larkin, 2003). The role of soil organisms in regulating ecosystem processes has received growing attention over the past several years and there is an increasing number of studies on questions such as how decomposers respond to disturbance regimes especially those related to agriculture (Guitian and Bardgett, 2000;Wardle et al, 1999;Yeates et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although agricultural practices induce general changes in soil microbial communities, specific microbial groups may respond differently. Clegg et al (6) showed that the application of inorganic nitrogen had a significant impact on eubacterial and actinomycete community structures, whereas soil drainage significantly affected the community structures of actinomycetes and pseudomonads. In addition, continuous wheat cropping affected the community structure of pseudomonads, such that an increase in the population of antibiotic-producing Pseudomonas spp.…”
mentioning
confidence: 99%
“…Since microbial populations play an important role in plant residue decomposition and nutrient cycling, it has been an area of interest to study how fertilizers affect the structure and function of these microbes. By using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) and phospholipid fatty acid (PLFA) profiling, Clegg et al, (2003) found that nitrogen fertilizer has a significant impact on the total bacterial and actinomycete community structures. It was also found that fertilizer amendment altered the abundance of bacterial groups throughout the agriculture soil in Watkisville, Georgia, USA by using both 16S rRNA gene clone libraries and PLFA (Jangid et al, 2008).…”
Section: Fertilizermentioning
confidence: 99%